The Influence of Dongklak Dance Learning on the Perception of Students at the Indonesian School of Kuala Lumpur (SIKL) Regarding Indonesian Culture - Nabila, Jihan; Winarti, Puji; Legowo, Yogi Ageng Sri (Universitas Syiah Kuala, 2025)
Indonesia is known for its social diversity, which includes ethnicities, cultures, religions, and customs. The principle of